Comparative study on modelling concrete properties using physical and mechanical properties of recycled coarse aggregate. (22nd August 2022) - Chen, Xiaoguang; Capiau, Laurent; Reynaert, Ibbe; Zheng, Kai; Gruyaert, Elke; Li, Jiabin
Highlights: Particle density and water absorption may not always be sufficient to characterize the quality of RA. Micro-Deval coefficient and Los Angeles coefficient of RA correlate well with mechanical properties of RAC. Salt scaling, capillary absorption and bulk mortar's porosity tended to be independent of RA quality. Abstract: Two physical properties of recycled aggregate (RA), namely oven-dried particle density ( ρ r d ) and water absorption ( WA 24 ), are commonly used to characterize the quality of RA and to model the properties of recycled aggregate concrete (RAC). This approach suffers from several drawbacks, including high variability in WA 24, overestimation of absorbed water due to the decomposition of hydrates during drying at (110 ± 5) °C, neglect of absorption kinetics, and insufficient consideration of old interfacial transition zone in RA. As an alternative, this study evaluates whether two mechanical properties of RA, namely micro-Deval coefficient ( M DE ) and Los Angeles coefficient ( LA ), can realistically describe the relationship between the properties of RA and RAC. Correlation analysis was conducted using data from this study and the literature. Results showed that the compressive strength, tensile splitting strength, modulus of elasticity and surface electrical resistivity of RAC varied in proportion to those four properties of RA, whilst the freeze-thaw resistance with de-icing salts, capillary absorption and bulk mortar's porosity tended to be independent of RA quality. When estimating the mechanical properties of RAC, LA and M DE are valid indicators as alternatives to or simultaneously with ρ r d and WA 24 .